Strategies for sustainable upgrading in global value chains: The Ivorian and Ghanaian cocoa processing sectors - Jan Grumiller; Hannes Grohs; Werner Raza; Cornelia Staritz; Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2018)
This policy note presents policy recommendations for a sustainable development strategy targeting the Ivorian and Ghanaian cocoa processing sectors. Against the backdrop of a comparatively small share of processed cocoa exports and limited opportunities in the cocoa global value chain, industrial policies should primarily seek to leverage the increasing opportunities in the local and regional as well as in niche global export markets to further promote local value added and linkages through the processing of cocoa beans. This is particularly important in the context of the Economic Partnership Agreements (EPAs) that both countries have negotiated with the EU.
Keywords: 330